Reliability of wavefront shaping based on coherent optical adaptive technique in deep tissue focusing. Issue 1 (7th November 2019) - Hu, Lejia; Hu, Shuwen; Li, Younong; Gong, Wei; Si, Ke
Abstract: Wavefront shaping can compensate the wavefront distortions in deep tissue focusing, leading to an improved penetration depth. However, when using the backscattered signals as the feedback, unexpected compensation bias may be introduced, resulting in focusing position deviations or even no focus in the illumination focal plane. Here we investigated the reliability of wavefront shaping based on coherent optical adaptive technique in deep tissue focusing by measuring the position deviations between the foci in the illumination focal plane and the epi‐detection plane. The experimental results show that when the penetration depth reaches 150 μm in mouse brain tissue (with scattering coefficient 22.42 mm −1 ) using a 488 nm laser and an objective lens with 0.75 numerical aperture, the center of the real focus will deviate out of one radius range of the Airy disk while the optimized focus in the epi‐detection plane maintained basically at the center. With the penetration depth increases, the peak to background ratio of the focus in the illumination focal plane decreases faster than that in the epi‐detection plane. The results indicate that when the penetration depth reaches 150 μm, feedback based on backscattered signals will make wavefront shaping lose its reliability, which may provide a guidance for applications of non‐invasive precise optogenetics or deep tissue optical stimulation using wavefront shaping methods. A, Intensity distribution in the epi‐detection plane and the illumination focal plane before and after correction, corresponding to brain sections with 250 and 300 μm thickness, respectively. Scale bar is 2 μm. B, Averaged focusing deviations in the epi‐detection plane (optimized) and the illumination focal plane (monitored) after compensation. The unit of the ordinate is one Airy disk diameter. Black dashed line represents one Airy disk radius. Bars represent the SE of each measurement set. Abstract : The reliability of wavefront shaping in mouse brain tissue focusing is investigated by using backscattered light as feedback. Statistical results show that when the penetration depth of 488 nm laser reaches 200 μm, the focus on the epi‐detection plane is optimized but no effective focusing is reconstructed in the illumination focal plane, which is of importance to improve the epi‐detection based wavefront shaping methods in biological applications.